Incidence and impact of venous thromboembolism in hospitalized patients with Crohn's disease. Issue 219 (November 2022) - Keller, Karsten; Sivanathan, Visvakanth; Schmitt, Volker H.; Ostad, Mir A.; Münzel, Thomas; Espinola-Klein, Christine; Hobohm, Lukas
Abstract: Background: Crohn's disease (CD) is associated with an increased risk for venous thromboembolism (VTE). Beside higher VTE risk, data on impact of VTE on survival and risk factors for the occurrence of VTE in CD are sparse. Methods: The German nationwide inpatient sample was screened for patients admitted due to CD (ICD-code K50). CD hospitalizations were stratified for VTE and risk-factors for VTE and impact of VTE on in-hospital case-fatality rate were investigated. Results: Overall, 333, 975 hospitalizations of patients due to CD were counted in Germany (median age 38.0 [IQR 24.0–52.0] years, 56.0 % females) during the observational period 2005–2018. VTE rate increased slightly from 0.6 % (2005) to 0.7 % (2018) (β 0.000097 [95%CI 0.000027 to 0.000167], P = 0.007) 2005–2018 and with age-decade (β 0.0017 [95%CI 0.0016 to 0.0019], P < 0.001). In total, 0.7 % (2295) of the CD inpatients had a VTE event. Patients with VTE were in median 12 years older (49.0 [34.0–62.0] vs. 37.0 [24.0–52.0] years, P < 0.001) and colon-involvement was in those patients more prevalent (32.0 % vs.27.7 %, P < 0.001). Age ≥ 70 years, obesity, colon-involvement, cancer, surgery, thrombophilia, and heart failure were strongly associated with higher risk of VTE in CD patients. In-hospital death occurred 15-times more often in CD with VTE than without (4.5 % vs. 0.3 %, P < 0.001). VTE was independently associated with increased in-hospital case-fatality rate (OR 9.31 [95%CI 7.54–11.50], P < 0.001). Conclusions: VTE is a life-threatening event in hospitalized CD patients associated with 9.3-fold increased case-fatality rate. Older age, obesity, colon involvement, cancer, surgery, thrombophilia and heart failure were strong risk factors for VTE in CD. Highlights: Prevalence of Crohn's disease (CD) is high in North America and in Europe. CD is considered as a risk factor for venous thromboembolism (VTE). VTE is a life-threatening event in CD patients with 9.3-fold increased case fatality rate. Colon involvement was identified as strong risk factors for VTE in CD.